The Sweetpotato - Loebenstein, Gad; Thottappilly, George (Springer Netherlands : Imprint: Springer, 2009)
In the last four decades of the twentieth century the use of sweetpotato was diversified beyond their classification as subsistence, food security, and famine-relief crop. In developing countries they serve both as human food and for feeding livestock. In Western countries they appeal to health conscious consumers because of their nutritional aspects. The sweetpotato is very high in nutritive value, and merits wider use on this account alone. The book has 2 parts. A general one giving up-to-date information on the history, botany, cultivars, genetic engineering, propagation, diseases and pests, nutritional data and marketing; and a second part presenting data on sweetpotato growing practices in different areas of the world. The information should be useful to researchers, practitioners and crop administrators in different countries.